Exploring cluster formation in uranium oxidation using high resolution X-ray spectroscopy at elevated temperatures - Elena F. Bazarkina; Stephen Bauters; Yves Watier; Stephan Weiss; Sergei M. Butorin; Kristina O. Kvashnina (Communications Materials)
Abstract Uranium dioxide (UO2) is a complex material with significant relevance to nuclear energy, materials science, and fundamental research. Understanding its high-temperature behavior is crucial for developing new uranium-based materials and improving nuclear fuel efficiency in nuclear reactors. Here we study the evolution of uranium state during the oxidation of UO2 in air at temperatures up to 550 °C using the in situ X-ray absorption spectroscopy in high energy resolution fluorescence detection mode at the U M4 edge, combined with electronic structure calculations. Our data reveal a complex sequence of events occurring over minutes and hours at elevated temperatures, including changes in the electronic and local structure, 5 f electron occupancy, the formation of U cuboctahedral clusters, and the creation of U4O9 and U3O7 mixed U oxide phases. These findings highlight the fundamental role of clustering processes and pentavalent uranium in both the oxidation process and the stabilization of uranium materials.